THE USE OF COMPETITOR ANALYSIS AS A FACTOR OF INCREASING THE COMPETITIVENESS OF THE COMPANY - U. A. Sharipova (American Journals, 2023)
Along with theoretical studies of the essence of competition and competitiveness, the problem of practical assessment of competitiveness has long been discussed in the economic literature. It can be stated that certain successes have been achieved in assessing the competitiveness of products to date, quite acceptable methods for assessing the competitiveness of identical goods and services have been developed.
Keywords: situation, complicate, assessment,competitiveness of enterprises